1991
DOI: 10.1207/s15327752jpa5601_11
|View full text |Cite
|
Sign up to set email alerts
|

Personality Assessment of the Prelingual, Profoundly Deaf Child or Adolescent

Abstract: Personality assessment of children and adolescents experiencing an early, profound hearing loss is hampered by the lack of instruments standardized and/or developed primarily for use with deaf clients. Further compounding the problem are the relatively few psychologists trained in and/or experienced with deaf personality assessment. This article reviews the rudimentary requirements for personality assessment with the deaf and critiques the available personality tests that are either used or useable in assessin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This last-mentioned study found not only a characteristic psychometric profile, but also evidence that such profiles are affected by administration procedures and by the use of norms that are based on people who were deaf (versus the standardization sample). In a review of personality assessment tools used with children and adolescents who are deaf, Cates and Lapham (1991) emphasized not only the lack of instruments developed for such applications, but also the lack of reliability and validity studies.…”
Section: Growth Of Rehabilitation-based Psychological Assessmentmentioning
confidence: 99%
“…This last-mentioned study found not only a characteristic psychometric profile, but also evidence that such profiles are affected by administration procedures and by the use of norms that are based on people who were deaf (versus the standardization sample). In a review of personality assessment tools used with children and adolescents who are deaf, Cates and Lapham (1991) emphasized not only the lack of instruments developed for such applications, but also the lack of reliability and validity studies.…”
Section: Growth Of Rehabilitation-based Psychological Assessmentmentioning
confidence: 99%